Reduced biofilm formation in Menaquinone-7 production process by optimizing the composition of the cultivation medium - Dinali Ranmadugala; Alireza Ebrahiminezhad; Merilyn Manley-Harris; Younes Ghasemi; Aydin Berenjian (Shiraz University of Medical Sciences, 2017)
Nutrient components in the culture medium can affect not only the growth and metabolic activity of bacteria, but also bacterial attachment to solid surfaces. Based on the fact that response surface methodology (RSM) has been successfully applied for the optimization of Menaquinone-7 (MK-7) production. The objective of this research was to investigate the feasibility of reducing biofilm formation with added nutrient components to the optimum medium previously described for MK-7 production without compromising MK-7 production. Monovalent and divalent salts and urea which were suspected to have an impact on bacterial biofilms were screened using a full factorial design.  Calcium chloride and urea were found to significantly influence the biofilm biomass and MK-7 production (p < 0.05). Central composite face design (CCF) was used for the optimization. The minimum biofilm biomass of 0.56g and MK-7 concentration of 17.98mg/L was achieved at the optimum conditions. This is the first report on biofilm reduction in the MK-7 production process through optimization of nutrient components.